2023
DOI: 10.3390/diagnostics13081393
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Prognostic Biomarkers CBX6 and CBX7 in Bladder Cancer

Abstract: Background: Chromobox (CBX) proteins are essential components of polycomb group proteins and perform essential functions in bladder cancer (BLCA). However, research on CBX proteins is still limited, and the function of CBXs in BLCA has not been well illustrated. Methods and Results: We analyzed the expression of CBX family members in BLCA patients from The Cancer Genome Atlas database. By Cox regression analysis and survival analysis, CBX6 and CBX7 were identified as potential prognostic factors. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Among these 27 prognostic DECRs, 23 risk and 4 protective CRs were identified. At present, many of these 27 prognostic CRs we identified have been shown to have correlations with prognosis in some cancers [48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Among these 27 prognostic DECRs, 23 risk and 4 protective CRs were identified. At present, many of these 27 prognostic CRs we identified have been shown to have correlations with prognosis in some cancers [48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 82%
“…Among these 27 prognostic DECRs, 23 risk and 4 protective CRs were identified. At present, many of these 27 prognostic CRs we identified have been shown to have correlations with prognosis in some cancers [ 48 52 ]. For example, CBX6 and CBX7 were identified as prognostic biomarkers in bladder cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously performed studies only considered a particular criteria for instance expression data, gene-specific approach, etc. to propose biomarkers 65 , 66 . Some research work proposed signature models with good performance but they all followed a different approach to create such gene sets and did not consider hallmark pathways along with other gentic fators 67 , 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies have indicated that, apart from tumor genetics, the abnormal regulation of epigenetics also has a crucial impact on the progression of PCa. Although the exact roles of CBXs in PCa are still not completely understood, previous studies have indicated that CBXs, which are essential constituents of epigenetic regulatory complexes, play signi cant roles in the advancement and growth of different types of cancer [16][17][18][19][20][21].This study involved a comprehensive examination of their expression patterns and explored their associations with clinical features, prognostic importance, in ltration of immune cells, and potential functions in PCa. By employing bioinformatics, we have created a prognostic model that incorporates CBX2 and demonstrates exceptional predictive precision.…”
Section: Discussionmentioning
confidence: 99%